If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5y + -3) = 56 Reorder the terms: -2(-3 + 5y) = 56 (-3 * -2 + 5y * -2) = 56 (6 + -10y) = 56 Solving 6 + -10y = 56 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -10y = 56 + -6 Combine like terms: 6 + -6 = 0 0 + -10y = 56 + -6 -10y = 56 + -6 Combine like terms: 56 + -6 = 50 -10y = 50 Divide each side by '-10'. y = -5 Simplifying y = -5
| 14-6-x= | | 3(x-3)-x=1 | | 144(x-10)=x(144-y) | | 8u+1=9 | | 3xsquared-0.75=90 | | xy-144x+1440=0 | | -29-5x=2(4x+5) | | 8-9v=26 | | 11x-104=64 | | 9+2(2p-1)=27 | | 11x-16=6+2 | | ln^2x+2lnx=0 | | 8u-u=u+12 | | x+2=(x-1)*(x+1) | | lnx+2lnx=0 | | x^2-4x^2+4x+1=0 | | v=bx | | X+8.4=-13.9 | | -4(1y+-1)=0 | | -2+3x=-3+8 | | 2x+8=-48-8x | | x^2+3x=65.7 | | -4+11n-15y-n= | | 29+29x=15+31x | | -9(7x+8)=-198 | | 4y+5+2y=13 | | -9(7+8)=-198 | | -3(x+9)+2x=5(x+10)-5 | | 29+29x=15+3x | | 2(r+5)=4r | | (10x-1)+(5x+6)= | | 275=60x+25(4) |